External beam radiation therapy for oral squamous cell carcinoma: A narrative review - Fahira, Jihan; Rifasky, Akmalisnani Putri; Pakphan, Mileniatri Evriany Lestari; Puspa L, Lusia Dinda; Putri, Yasmin Kamila; Darojah, Zakiyyah; Rohita Z, Dhea Rima; Ilhamuddin K, Haedar; Salwa SS, Jasmine; Benedictine O, Gabriella; Fadiyah, Malika; Rahmi, Adila Dzakiyya; Hurun’in, Arini; Fajrin, Farah Richana; Nurfitri, Aisyah Qonita; Azriella, Covina Reyhana; Diva, Annisa Tiara; Loveisca, Moza Zikra; Diandhary B, Ni Nengah; Wati, Sisca Meida (Indonesian Journal of Dental Medicine, 2025)
Background: Oral cancer is a malignancy that occurs in the oral cavity. Many factors cause oral cancer, namely alcohol consumption, tobacco smoking, smokeless tobacco, chronic irritation, and others. external beam radiation therapy (EBRT) is a technology commonly used in the standard treatment of head and neck cancer. Purpose: The aim of this review was to determine the effectiveness of EBRT for oral squamous cell carcinoma. Review: Lip carcinoma has a higher chance of healing compared to other cancers that usually appear in the neck and head. Lip carcinoma can be cured through radiation therapy, namely external beam radiation therapy (EBRT). EBRT can be combined withbrachytherapy, which can improve cancer healing. Conclusion: EBRT can be used for oral squamous cell carcinoma cancer treatment. However, there are some disadvantages of EBRT that need to be reviewed based on the conditions in the patient’s case.